Biometric of podal balance in draft horses to the Extension Program "Amigo do Carroceiro" do Centro de Ciências Agroveterinárias da Universidade do Estado de Santa Catarina in Lages/SC, Brazil Biometria do equilíbrio podal em equinos de tração pertencentes ao Programa de Extensão "Amigo do Carroceiro" do Centro de Ciências Agroveterinárias da Universidade do Estado de Santa Catarina no município de Lages/SC, Brasil - Schade J.* (2013)
The hooves of 44 horses registered in the Extension Program "Amigo do Carroceiro" do Centro de Ciências Agroveterinárias da Universidade do Estado de Santa Catarina (CAV-UDESC) were measured. The horses perform the function of traction in Lages, SC. The parameters evaluated were the frog length and width, lateral and medial heel length, angle and toe length and sole length and width. The following differences were observed: asymmetry between contralateral hoof of hind and forelimbs, toe angle overly acute, differences between hind and forelimbs in 40.9% and 34.1% respectively, bilateral contraction of the frog in the forelimbs (100%), right hind limb (70.5%) and left hind limb (66.0%). Medial-lateral hoof imbalance in the forelimbs (4.6 to 6.8%) and hind limbs (4.6 to 13.6%). Positive correlations were obtained (0.3 to 0.7) between body weight, sole length and width. Differences were observed between the hooves shoes and unshod, which were assigned to wear unshod hooves. It was also observed negligence of the wagoner about hoof care and frequency of trimming and shoeing, which was revealed by the high percentage of animals with loss of horseshoes.